CH3NH3PbI3 thin films prepared by hot-casting technique in the air: Growth mechanism, trap states and relating solar cells - Narit Faibut (2020)
© 2019 The Japan Society of Applied Physics. Tetragonal CH3NH3PbI3 perovskite thin films with large crystallite sizes were successfully fabricated under atmospheric air using a one-step hot-casting technique. The casting temperature governed structural and optical properties of the prepared films. The energy gaps of the hot-casted films changed with changing casting temperature due to the variation of Urbach energy. The hot-casted perovskite thin films had superior structural stability to that of the two-step method films. However, the hot-casted perovskite films contained trap states as suggested by additional emissions other than bimolecular recombination in photoluminescence spectra. The origins of these trap states were believed to be attributed to the presence of iodine vacancies (V I), iodine interstitial sites (I i) and methylammonium ion vacancies (V MA) in the prepared films. The fabricated perovskite solar cells showed that at low casting temperatures the power conversion efficiencies were relatively higher than the higher ones, this was attributed to their lower non-radiative recombination activities.